Use of VacA as a Vaccine Antigen - Mati Moyat; Dominique Velin (Toxins, 2016)
One of the major toxins secreted by H. pylori is the Vacuolating cytotoxin A (VacA) named after its ability to induce the formation of “vacuole”-like membrane vesicles in the cytoplasm of gastric cells. VacA has been associated with the disruption of mitochondrial functions, stimulation of apoptosis, blockade of T cell proliferation and promotion of regulatory T cells, thereby making it a promising vaccine target. Immunity to bacterial virulence factors is well known to protect humans against bacterial infections; hence, detoxified VacA has been evaluated as a vaccine antigen. Our short review summarizes the pre-clinical and clinical data that have been published on the use of VacA in the development of the H. pylori vaccine.